A Brazilian view on the epidemiology of allergic rhinitis - Pedro Miguel Goulart-Longo; Luiz Henrique Franciscatto; Eliane Mazzuco-Dos Santos; Chaiana Marcon (Revista Alergia México, 2019)
The article “Cross-sectional survey on the prevalence of allergic rhinitis in Argentina: the PARA study” gives an overview of the main epidemiological aspects of allergic rhinitis in Argentina. Allergic rhinitis is characterized by inflammation of the nasal mucosa; it’s triggered by exposure to allergens and mediated by IgE (immunoglobulin E). Due to its high prevalence in the urban population, it is being referred to as a disease of modern civilization. This letter seeks to complement the article with some epidemiological data on allergic rhinitis in Brazil and its comparison with Argentine data.